FAMILY SALAFI IDEOLOGY OF AL-IMAM ASH-SHAFI'I IN DUMAI - Muljo, Ariyani (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2016)
The purpose of this study was to determine how the Salafi doctrinal developments in the al-Imam ash-Shafi'i in Dumai. Salafi it is one of the methods in Islam who teaches Islamic law is pure without any addition and subtraction, based on the existing law on the generation of Muhammad and his companions, after they and the people afterwards. Where previously taken samples using Snowball Sampling and get respondents as many as 26 people,  headmaster, 1 teacher and 24 students. While data collection techniques used were non-test by using observation and interview guides. This study used descriptive qualitative method. Qualitative descriptive study was designed to collect information about the actual situations present while it lasted. The results obtained are Salafi doctrinal developments in the al-Imam ash-Shafi'i in Dumai very guided by the teachings salafi doctrine. Starting from salafi indications coming from the family, neighborhood and friends faith salafi, up to the ways teachers teach Salafi teachings to students, such as delivering materials based Salafi teachings on the sidelines of learning. Almost all of the ways it is guided by the Salafi doctrine, which led to the development of Salafi teachings in the al-Imam ash-Shafi'i, the better. Religious activity was often made to increase the depth of knowledge of students against the Salafi doctrine. In addition to the learning process is based on the teachings of salafi, this study also analyzes the teaching materials namely instructional handbook used in boarding school al-Imam ash-Shafi'i with teaching materials used public schools (non salafi). There are three points of difference from both the instructional materials, namely: The difference in the end result or conclusion; Material differences general and special; and materials that are not available (taught) in public schools